2020
DOI: 10.1111/mms.12760
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic occurrence, diel‐vocalizing pattern, and detection ranges of southern right whale gunshot sounds off South Africa's west coast

Abstract: Mate et al. (2011) showed that the coastal waters of the South African west coast are also used as an austral spring/summer feeding ground by the portion of the population that remains there year-round.Seasonal acoustic occurrence of SRWs in South African waters is currently based on short-term shallow coastal (adjacent to the coast and within the 100 m isobath) research (Figure 1; Hofmeyr-Juritz, 2010;Vinding-Petersen,-2016). An expansion of such acoustic work to more offshore waters (Figure 1) and more long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Half of the impulsive sounds (n ¼ 39) detected were recorded mid-morning, between 06:00 and 08:30. The impulsive sounds were structurally similar to the right whale "gunshot" (Parks et al, 2005;Shabangu et al, 2021) but were detected simultaneously (within 6 10 s) with other known humpback whale calls (whups and grumbles) strongly indicating that they are produced by humpback whales. All call types were more prevalent in the early morning and late evening (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Half of the impulsive sounds (n ¼ 39) detected were recorded mid-morning, between 06:00 and 08:30. The impulsive sounds were structurally similar to the right whale "gunshot" (Parks et al, 2005;Shabangu et al, 2021) but were detected simultaneously (within 6 10 s) with other known humpback whale calls (whups and grumbles) strongly indicating that they are produced by humpback whales. All call types were more prevalent in the early morning and late evening (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Impulsive sounds (gunshot-like calls) were also detected regularly at Vema. Until now, impulsive gunshots had only been associated with other baleen whale species-notably bowhead whales, who do not inhabit the region (Best, 2007), and right whales (Shabangu et al, 2021;Stafford et al, 2008). Right whale calls are readily detected in South African waters (Hofmeyr-Juritz and Best, 2011), and gunshot sounds in offshore waters between Vema and South Africa have been attributed to southern right whales (Shabangu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, such diel and seasonal variations could be due to seasonal changes in NLs (Fig. 2) and oceanographic conditions affecting the position of the thermocline (Shabangu et al 2020c). Similarly, Merkens et al (2019) observed no single diel pattern across locations in the Pacific Ocean.…”
Section: Discussionmentioning
confidence: 96%
“…AAR4 deployed at 4481 m water depth produced the lowest percentage of sperm whale acoustic occurrence, indicating that a small proportion of this species occupies this deep sea area, as similarly indicated by whale catches (Best 1999) and species distribution modelling (Purdon et al 2020b). Furthermore, sperm whale clicks produced at great depths could have been deflected by the thermocline (an acoustic barrier) and prevented from reaching AARs 1 and 4, as these 2 recorders were sometimes positioned above or below the thermocline depth (~200 m depending on season; Shabangu et al 2020c). On the other hand, AARs 2 and 3 were well positioned to detect sperm clicks as they were well below the thermocline depth throughout the year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation